Cervical length measurement by transvaginal sonography in predicting preterm labour in low risk women - P., Sandeep Sethumadhavan; Agarwal, Raju; M. Anilkumar, Jayamol; Ramchandran Pillai, Anup (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preterm birth is the leading cause of perinatal morbidity and mortality. Transvaginal sonographic measurement of the cervix is a reliable alternative method for the assessment of cervical length as it allows better quality and more accurate visualization of the uterine cervix. Several studies have reported that cervical assessment on transvaginal sonography may be useful in the prediction of preterm delivery. The objective of this study was to assess cervical length at 20 to 24 weeks of gestation in low risk women and correlate with the gestational age at delivery. Methods: A prospective cohort study conducted in a tertiary care Military Hospital in Pune, India. 354 asymptomatic low risk antenatal women with gestational age of 20 to 24 weeks were studied. Cervical assessment with transvaginal sonography for the measurement of cervical length was performed using a 10 MHz transvaginal probe. Results: 7 percent women delivered preterm. The incidence of short cervix in low risk women was only 0.56%. 100% women with short cervix delivered preterm and, only 6.9% patients who had cervical length more than 25 mm delivered preterm. Cervical length 25 mm has got sensitivity and NPV of 100% and a specificity of 93.46%. However, the PPV was only 8%. Conclusions: The study reported significant inverse relation between short cervix and the occurrence of preterm delivery. Our findings suggest that cervical length can be used as a screening method for preterm labour in low risk women. However strong evidences from large randomized control trials would be required to assess its cost-effectiveness.